FRI0333 B-cells depletion as rescue therapy for extra-criteria manifestations of primary antiphospholipid syndrome. (12th June 2018) - Sciascia, S.; Radin, M.; Cecchi, I.; Rubini, E.; Rossi, D.; Bazzan, M.; Roccatello, D.
Abstract : Background: While immunosuppressive drugs may be helpful in patients with active systemic autoimmune diseases, their use in antiphospholipid syndrome (APS) is still controversial, and mainly limited to very selected cases of catastrophic APS or in severe cases refractory to standard therapy. 1 B-cells are likely to play a central role in the generation of the aPL-induced clinical manifestations of the disease, so they might constitute a logical therapeutic target in APS. Objectives: To investigate PAPS patients with extra-criteria manifestations of APS treated with Rituximab (RTX) as a rescue therapy. Methods: We retrospectively retrieved data from patients who attended the S. Giovanni Bosco Hospital, Turin, Italy, who met the following inclusion criteria: a) persistent aPL positivity and fulfilled the Sydney criteria for PAPS[ 2 b) presented with at least 1 extra-criteria manifestation; c) were treated with RTX as a rescue therapy (e.g. because they were refractory/intolerant/contraindicated to standard therapy) for the management of extra-criteria manifestations of APS. Results: This retrospective study included 7 consecutive PAPS patients [median age 53 (range 38–66), female 6:1]. Table 1 resumes the characteristics of the PAPS patients included in the study. Six patients presented with severe thrombocytopenia (plts <50.000/mm 3 ) and 1 patient presented with recurrent superficial venous thrombosis (3 events in 6 months despite ongoing anticoagulation therapy with VKA). Previous therapies included intravenous immunoglobulins (5 patients) and high doses of steroids (3 patients). One patient received RTX as rescue therapy as a steroid-sparing agent because of the high cardiovascular risk (high body mass index, uncontrolled arterial hypertension, and diabetes). We observed a full response after treatment with RTX in 6 out of 7 patients (86%, 5 with thrombocytopenia and 1 with recurrent superficial thrombosis). One patient who did not respond to the B-cell depletion therapy, and was treated with a splenectomy 1 month after RTX therapy and platelets levels normalised 3 months after the procedure. Overall, median time free from relapse was 27.5 months (range 4–97), no adverse events were reported, no patients developed infections. Conclusions: In selected case of patients with PAPS, RTX can represent a safe and efficacious therapeutic tool to manage the extra-criteria manifestations of the syndrome, especially when standard approaches have failed or cannot be pursued. References: [1] Erre GL, Pardini S, Faedda R, Passiu G. Effect of rituximab on clinical and laboratory features of antiphospholipid syndrome: a case report and a review of literature. Lupus2008;17:50–5. doi:10.1177/0961203307085251 [2] Miyakis S, Lockshin MD, Atsumi T, Branch DW, Brey RL, Cervera R, et al. International consensus statement on an update of the classification criteria for definite antiphospholipid syndrome (APS). J Thromb Haemost2006;4:295–306. doi:10.1111/j.1538-7836.2006.01753.x Disclosure of Interest: None declared